Does Universalization of Healthwork? Evidence from Health Systems Restructuring and Expansion in Brazil - Sonia R. Bhalotra; Rudi Rocha; Rodrigo R. Soares (Institute of Labor Economics (IZA), 2019)
We investigate universalization of access to health in Brazil. We find large reductions in maternal, foetal, neonatal and post-neonatal mortality, a reduction in fertility and, possibly on account of selection, no change in the quality of births. Using rich administrative data, we investigate changes in organization, access and outcomes, thereby illuminating the driving mechanisms. We find sharp increases in coverage of primary health facilities with GPs and outreach workers and, in line with this, increases in outpatient procedures, prenatal care visits, health-education activities and home visits by medical professionals. Consistent with an attempt to rationalize use of hospital resources, we find a decline in specialists and hospital beds per capita. Despite this, we see increases in hospital births, C-sections, and maternal hospitalization for complications, with no change in rates of infant hospitalization.
Keywords: I12; I18; J10; J13; J24; O54; 330; universal health coverage; health systems; primary care; maternal mortality; infant mortality; birth outcomes